The Role of Governance in Agricultural Expansion and Intensification a Global Study of Arable Agriculture - Mandemaker, Menno (Ecology and Society, 2011)
ABSTRACT. In this research we studied empirical relationships between agricultural production dynamics and six quantitative World Bank governance indicators for 173 countries between 1975 and 2007. It is hypothesized that in countries with lower quality of governance, agricultural production increases are more likely to be achieved by area expansions than by increases in yields. We distinguished four groups of countries: those with both area and yield increases; those with increasing yields but decreasing area; those with decreasing yields but a growing area; and those with both declines in yields and area. We analyzed differences between these four groups, and also analyzed governance-production relationships within these groups. On average, quality of governance is low in countries with both area and yield increases and high in countries with increasing yields but decreasing area. Countries with declining yields were too few in number to allow for quantitative analyses. The analysis of governance-production relationships within the four groups suggests that countries with a lower quality of governance are more inclined to achieve production increases by expanding agricultural area rather than increasing yields. Additional explanatory value of governance indicators to agricultural production dynamics is generally small, but nevertheless significant in most cases. Our results suggest that, in order for agricultural production to increase without excessive expansions of agricultural area, governance issues should be resolved.